Invasion and escalation of Aleurodicus rugioperculatus: An alarming pest in east coast region of India - SINGH, SATYAPRIYA; SAMANT, DEEPA; SAHOO, MANAS RANJAN; KISHORE, KUNDAN; JINGER, DINESH; ACHARYA, GOBINDA CHANDRA (The Indian Journal of Agricultural Sciences, 2022)
In nutshell, invasive species causes serious threat to the natural ecosystem. Severe and up surging phenomenon of exotic rugose spiraling whitefly (RSW), Aleurodicus rugioperculatus (Martin) became a major concern in global crop production. The present study aimed to document and assesses the host range, nature and intensity of damage caused by this cryptic species. The roving survey was conducted to study the occurrence of RSW in the fruit orchards, vegetable gardens, ornamental crops and avenues trees plantation in the east-coast region of India. Hierarchical clustering was performed based on its incidence on different host plants and correlated with the dissimilarity index. The RSW was identified based on morphological characteristics and the nature of the damage. RSW infested a total of 27 crops. Four host plants, viz. Cocos nucifera (L.), Musa sp. Psidium guajava (L.) and Syzygium cumini (L.) (Skeels) showed severe levels of infestation. An important implication from the current study is the occurrence of its incidence on the two new host crops, viz. Amaranthus tricolor (L.) and Solanum torvum that was envisaged firstly to the scientific world. This study provides baseline information about RSW among various stakeholders, helps to develop a sustainable management strategy for timely mitigation of RSW menace.